2021
DOI: 10.1038/s41419-021-03820-7
|View full text |Cite
|
Sign up to set email alerts
|

Upregulated PPARG2 facilitates interaction with demethylated AKAP12 gene promoter and suppresses proliferation in prostate cancer

Abstract: Prostate cancer (PCA) is one of the most common male genitourinary tumors. However, the molecular mechanisms involved in the occurrence and progression of PCA have not been fully clarified. The present study aimed to investigate the biological function and molecular mechanism of the nuclear receptor peroxisome proliferator-activated receptor gamma 2 (PPARG2) in PCA. Our results revealed that PPARG2 was downregulated in PCA, and overexpression of PPARG2 inhibited cell migration, colony formation, invasion and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…6 E). Previous studies demonstrated that knockout or silencing of AKAP12 activates the PI3K/AKT pathway [ 32 , 33 ]. Therefore, cell lines were constructed with AKAP12 overexpression plasmids, which revealed that AKAP12 overexpression inhibited the PI3K/AKT pathway ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…6 E). Previous studies demonstrated that knockout or silencing of AKAP12 activates the PI3K/AKT pathway [ 32 , 33 ]. Therefore, cell lines were constructed with AKAP12 overexpression plasmids, which revealed that AKAP12 overexpression inhibited the PI3K/AKT pathway ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A colony formation assay was conducted as previously described [ 20 ]. Briefly, PCa cells were seeded onto 6-well plates at 1000 cells per well, treated with deslanoside at 0, 60, and 120 nM for 13 days for 22Rv1 cells and 0, 40, and 80 nM for 10 days for PC-3 and DU 145 cells.…”
Section: Methodsmentioning
confidence: 99%
“…miR-200b-3p can exert different functions depending on the type of tumor. For instance, in most cases, it exhibits tumor-suppressive effects and is therefore downregulated, with examples of such tumors being colorectal cancer (CRC) (4-7), hepatocellular carcinoma (HCC) (8)(9)(10)(11)(12), pancreatic cancer (13,14), gastrointestinal stromal tumors (15), breast cancer (16)(17)(18), melanoma (19), glioblastoma (20), glioma (21), thyroid carcinoma (22), cemento-ossifying fibroma (23), esophageal cancer (24,25), oral squamous cell carcinoma (26), prostate cancer (27,28), renal cell carcinoma (29), bladder cancer (30), and malignant mesothelioma (31). However, as already noted, this microRNA can also be oncogenic in various types of cancers, with examples of such tumors being prostate cancer (32,33), lung cancer (34)(35)(36)(37)(38), oral squamous cell carcinoma (39), esophageal squamous cell carcinoma (40), breast cancer (41), colorectal cancer (42,43), neck cancer (44), cholangiocarcinoma (45), and hepatocellular carcinoma (46).…”
Section: Mir-200b-3p Function Is Dependent On Cancer Typementioning
confidence: 99%
“…The former, as an oncogene (53), is not only involved in adipogenesis but is also significantly upregulated in metastatic lesions compared with primary tumors in prostate cancer (53). In contrast, the protein products of DNMT3A/3B are both enzymes that act on DNA sequences to catalyze the methylation of CpG and by targeting DNMT3A/3B, miR-200b-3p facilitates interactions between peroxisome proliferator-activated receptor γ 2 (PPARG2) and demethylated A-kinase anchoring protein 12 (AKAP12) gene promoter to suppress the growth of prostate cancer (27). However, Janiak et al found that, in prostate cancer, miR-200b-3p could even regulate the level of tissue inhibitor of metalloproteinase 4 (TIMP4) expression (33), with this regulation being mediated by ZEB1 and ETS proto-oncogene 1 (ETS1) which represent two targets of miR-200b-3p (33).…”
Section: Mir-200b-3p and Its Functions In Hepatocellular Carcinomamentioning
confidence: 99%